After fidel raul castro and the future of Cuba's revolution - Latell, Brian (Palgrave Macmillan, 2007)
This is a compelling behind-the-scenes account of the extraordinary Castro brothers and the impending dynastic succession of Fidel's younger brother Raul. Brian Latell, the CIA analyst who has followed Castro since the sixties, gives an unprecedented view into Fidel and Raul's remarkable relationship, revealing how they have collaborated in policy making, divided responsibilities, and resolved disagreements for more than forty years--a challenge to the notion that Fidel always acts alone. Latell has had more access to the brothers than anyone else in this country, and his briefs to the CIA informed much of U.S. policy. Based on his knowledge of Raul Castro, Latell makes projections on what kind of leader Raul would be and how the shift in power might influence U.S.-Cuban relations.